Optimalisasi Prosedur Administrasi Piutang untuk Peningkatan Efisiensi pada Pedagang Besar Farmasi (PBF) - Nurluthfi Oktavia, Ulla; Ratnawati, Dyah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to evaluate and optimize accounts receivable administrative procedures in order to improve operational efficiency in Pharmaceutical Wholesalers (PBF). Well-structured and effective receivables management is a key factor in maintaining corporate liquidity, accelerating cash turnover, and minimizing the risk of uncollectible accounts that may disrupt financial stability. This research employs a case study method with a qualitative descriptive approach through direct observation of receivables administration activities, collection processes, and the reporting system implemented by the company. The results indicate that the implementation of an Accounting Information System (AIS) for receivables has contributed positively to the accuracy of transaction recording, the availability of receivables information, and the strengthening of internal control. Invoice verification procedures, segregation of duties among functions, and systematic documentation have proven effective in supporting data accuracy and facilitating audit trails. However, this study also identifies several weaknesses that affect the efficiency of receivables management, including the lack of full integration between sales and finance systems, the continued reliance on manual credit approval processes, and the underutilization of system-based receivable reminder features. Empirically, these conditions lead to delays in updating receivable status, increased administrative workload, and suboptimal credit risk control, particularly for receivables outstanding for more than 90 days. This study recommends the development of an integrated AIS, the implementation of automated credit approval based on customer payment history, and the utilization of real-time receivables reminder systems and data analytics. By adopting these recommendations, companies are expected to enhance operational efficiency, accelerate receivables turnover, and maintain sustainable cash flow performance. The findings of this study may serve as a practical reference for other pharmaceutical distribution companies in strengthening receivables management through information systems